2011
DOI: 10.1111/j.1365-2486.2011.02449.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on forest herbs assessed by warming and transplant experiments along a latitudinal gradient

Abstract: Slow-colonizing forest understorey plants are probably not able to rapidly adjust their distribution range following largescale climate change. Therefore, the acclimation potential to climate change within their actual occupied habitats will likely be key for their short-and long-term persistence. We combined transplant experiments along a latitudinal gradient with open-top chambers to assess the effects of temperature on phenology, growth and reproductive performance of multiple populations of slow-colonizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
144
7
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(166 citation statements)
references
References 71 publications
(94 reference statements)
11
144
7
4
Order By: Relevance
“…The use of soil transplant as a proxy to study the effects of global changes has been successfully demonstrated in both plant biology and microbiology (Balser and Firestone, 2005;Breeuwer et al, 2010;De Frenne et al, 2011;Lazzaro et al, 2011;Vanhala et al, 2011). It was reported that soil microbial community structure and community functions were altered when soil was transplanted into warmer regions to simulate global warming (Vanhala et al, 2011), which was consistent with a number of studies showing that warming altered microbial community (Petchey et al, 1999;Rinnan et al, 2007;Zhou et al, 2012).…”
Section: Introductionsupporting
confidence: 63%
“…The use of soil transplant as a proxy to study the effects of global changes has been successfully demonstrated in both plant biology and microbiology (Balser and Firestone, 2005;Breeuwer et al, 2010;De Frenne et al, 2011;Lazzaro et al, 2011;Vanhala et al, 2011). It was reported that soil microbial community structure and community functions were altered when soil was transplanted into warmer regions to simulate global warming (Vanhala et al, 2011), which was consistent with a number of studies showing that warming altered microbial community (Petchey et al, 1999;Rinnan et al, 2007;Zhou et al, 2012).…”
Section: Introductionsupporting
confidence: 63%
“…Passive warming [1][2][3][4][5][6][7]. Previous warming studies using OTCs have been directed toward analyzing specific species responses [8], radiation dynamics [9], plant phenology [10], snow regime shifts [11], and trace gas exchange [12,13] to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Previous warming studies using OTCs have been directed toward analyzing specific species responses [8], radiation dynamics [9], plant phenology [10], snow regime shifts [11], and trace gas exchange [12,13] to name a few. Studies have spanned multiple locations to include gradients; DeFrenne et al [5,6] examined transplants of forest understory species along a latitudinal gradient, and Oberbauer et al [13] studied ecosystem CO 2 fluxes in response to latitudinal and moisture gradients. Meta-analyses of many sites combined have quantified the impacts of passive warming treatments on tundra vegetation and indicate a warming climate in high latitudes and high elevations is changing plant communities and ecosystem function [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, our results clearly point out the influence of seed provenance on seedling responses to climate change (Atzmon et al, 2004;Thiel et al, 2014). Additionally, the possibility of the presence of local adaptations should be analysed (Kawecki and Ebert, 2004) through the use of, for instance, transplant experiments (De Frenne et al, 2011;HilleRisLambers et al, 2013;Ibáñez and McCarthy-Neumann, 2014).…”
Section: Discussionmentioning
confidence: 80%